Peran Pendidikan Agama dalam Mencegah Kenakalan Remaja di Masyarakat - Deassy Arestya Saksitha; Rio Agus Susanti; Anisa; Andi Nurfadilah; Helmi Iskandar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
In Indonesia, the rate of juvenile delinquency has reached 23.46%. With various types of cases, the prevalence of juvenile delinquency in today’s society poses a very serious challenge and requires a comprehensive approach. This study aims to analyze the role of Islamic Religious Education (PAI) as a preventive and curative tool in addressing juvenile delinquency in society. Using a qualitative research method with a literature review approach, data were collected from various scientific literature, books, and relevant journals and then analyzed using content analysis techniques. The results of the study indicate that Islamic Religious Education through the instillation of noble moral values, the strengthening of religious faith, and guidance in religious practice also plays a crucial role in building a moral foundation for adolescents. Within the community, the effectiveness of PAI heavily depends on the synergy among the three pillars of education: the family, the school, and community religious leaders. Furthermore, adolescents’ active participation in community religious activities such as mosque youth groups and religious study circles has been shown to significantly reduce the tendency toward deviant behavior. The conclusion of this study affirms that Islamic Religious Education is not merely the transfer of theological knowledge but rather an adaptive character building system that guides adolescents in navigating the social dynamics of society.